Oviposition and feeding behaviour of Xanthopimpla pedator (Fabricius) (Hymenoptera: Ichneumonidae) on tropical tasar silkworm, Antheraea mylitta (Drury) (Lepidoptera: Saturniidae) - Gathalkar, G.B. (Journal of Asia-Pacific Entomology, 2017)
Xanthopimpla pedator is a major pupal endoparasitoid of tropical tasar silkworm, Antheraea mylitta. Extensive parasitism by X. pedator results in pupal (seed) mortality and broken cocoons, which declines the wild tasar silk production. A detailed account is given on the oviposition behaviour of the female X. pedator and feeding behaviour of its immature forms in the pupa of A. mylitta. Scanning electron microscopic (SEM) details of the ovipositor of X. pedator revealed the presence of various mechano- and chemoreceptors, which regulate host discrimination and oviposition behaviour. The oviposition and feeding behaviour of X. pedator were evaluated in the field as well as in situ conditions. In addition, the invasion caused by X. pedator on A. mylitta, are also described. Host-parasitoid interactions are also discussed and recorded frame-by-frame video-graphically. The parasitoid X. pedator, arrests development and eventually the survival of A. mylitta. We also assume that parasitism by X. pedator in tasar culture is due to the microhabitat and food content of pupal host A. mylitta, which favors the development of parasitoid.